Prospects for fisheries development in dead rivers: Case studies in the state of Odisha, India - Sahoo, A K; Das, B K; Sajina, A M; Samanta, S; Kumar, V; Roshith, C M; Koushlesh, S K; Das, S K; Meena, D K; Swain, H S; Mohanty, B P (Journal of the Inland Fisheries Society of India, 2021)
Reduced water flow has become one of the major threats for the sustenance of river ecosystem in recent years. Due to reduced flows, many rivers have lost their natural characteristics. Furthermore, many rivers particularly in the deltaic regions, which are distributaries of some other rivers, have been artificially blocked to protect from the flood situation, and in subsequent years due to loss of connectivity, these small distributaries have been changed into zero flows channels or dead river structures. An investigation was undertaken in four identified dead rivers in the Mahanadi river delta viz., Chhinda and Paika in Cuttack district, and Alaka and Balia in Jagatsinghpur district of Odisha during the lean period of 2018-19. The investigation was made through direct field observation and both biotic and abiotic sample analysis. Each dead river was classified into three stretches/zones based on the availability of water flows and channel morphology as (i) Dry zone or zero water flows throughout the year and experience of water flows only during floods, (ii) Seasonal flows zone only during monsoon and remains dry rest of the seasons,(iii) Pools with stagnant water during lean season and receives water during monsoon. Based on the hydrological dynamics, fish species diversity and physico-chemical parameters of the water available in channel pockets, it is recommended that Culture-based fisheries (CBF) for the river stretch that holds water as small pockets during the lean season(zone-iii), indigenous fish species stock enhancement programme, and enclosure farming techniques especially pen culture in the stretch, where water availability is seasonal (zone-ii) and developing nursery and grow-out ponds, restricted maximum encroachment length of Â¼ of total channel width (m) for aquaculture of indigenous fish species (zone-i). While, in zone-i, length of 3/4thof total channel width (m) should be left for maintaining natural flushing during flood season. Our study observed that fish species such as Cirrhinus reba, Puntius spp. and Amblypharyngodon mola, could be the better fish species for fish production enhancement through both enclosure and pond based culture systems ensuring the nutritional and livelihood of fishermen. In Balia channel bed, ponds were stocked with carps and with A. mola with annual production of 4.5 tonnes. However, in Balia and Alka (zone-i), two serious concerns have been noticed: (a) channel bed coverage for aquaculture without proper investigation, (b) introduction of exotics like Piaractus brachypomus for pond based culture. This study is of its first kind and underlines the possibilities of scientific fisheries development through the effective utilization of these resources in dead rivers. As the report is based on a preliminary investigation, more such studies are required to identify and map dead rivers in India, and to develop a package of practices for fisheries development without environmental damage. Key words Dead rivers; Fisheries development; Odisha; India